Kepuasan Pengunjung Taman Buah Mekarsari Bogor Berdasarkan Indikator Destinasi Pariwisata Berkelanjutan pada Masa Pandemi COVID-19 - ANDIKA, KARTIKA DEWI; WIDHIANTHINI, WIDHIANTHINI; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Visitors’ Satisfaction of Mekarsari Fruit – Botanical Garden Bogor during COVID-19 Pandemic based on Sustainablilty-Continuous Tourism Indicator Biodiversity conservation center of tropical fruits, from all regions in Indonesia and other world commonly known as Mekarsari. Mekarsari also a place of cultivation research, breeding and propagation of superior seeds. It is one of the most visited tourist spot in Bogor city. This pandemic make the tourism industry out due to the declining number of visitors. Many tourist places closed because they were unable to survive the difficult time of the covid-19 pandemic. Mekarsari has also been heavily hit a decline in visitors over the last few years. One of the factors that led was the implementation of Community Activity Restrictions (PPKM) during this pandemic. It is therefore to be feared that the tourism Mekarsari Fruit Garden will not be able to offer any satisfaction to visitors. The objective of this study is for researchers to evaluate visitor satisfaction according to sustainable tourism criteria including tourism management, economic (tourism costs), socio-cultural and environmental aspects. So that based on the results of the level of satisfaction, it can be seen that the priority factors are the satisfaction of visitors to Mekarsari Fruit Garden. The research method in this study uses a quantitative descriptive method, using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) analysis methods. The sample collected from this study was 100 field respondents. The results of this study, namely the satisfaction of agro-tourism visitors at Mekarsari Fruit Garden as a whole, is in the "Satisfied" category with a total score of 69.90. Factors that are the main priority for improvement are tourist attraction facilities and play areas, parking lots, access for individuals with disabilities, entry prices, body temperature checks, beauty and scenery of tourist objects, tidiness and cleanliness in the tourist environment.